How many kingdoms of life? Eukaryotic phylogeny and philosophy of systematics - Lamża, Lukasz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2019)
According to contemporary understanding of the universal tree of life, the traditionally recognized kingdoms of eukaryotic organisms—Protista, Fungi, Animalia and Plantae—are irregularly interspersed in a vast phylogenetic tree. There are numerous groups that in any Linnaean classification advised by phylogenetic relationships (i.e. a Hennigian system) would form sister groups to those kingdoms, therefore requiring us to admit them the same rank. In practice, this would lead to the creation of ca. 25-30 new kingdoms that would now be listed among animals and plants as “major types of life”. This poses problems of an aesthetic and educational nature. There are, broadly speaking, two ways to deal with that issue: a) ignore the aesthetic and educational arguments and propose classification systems that are fully consistent with the Hennigian principles of phylogenetic classification, i.e. are only composed of monophyletic taxa; b) ignore Hennigian principles and bunch small, relatively uncharacteristic groups into paraphyletic taxa, creating systems that are more convenient. In the paper, I present the debate and analyze the pros and cons of both options, briefly commenting on the deeper, third resolution, which would be to abandon classification systems entirely. Recent advances in eukaryotic classification and phylogeny are commented in the light of the philosophical question of the purpose and design principles of biological classification systems.